Hemorrhagic bullous lesions in Henoch-Schönlein purpura: a case report and review of the literature - Hung-Wen Su; Chiu-Yu Chen; Yee-Hsuan Chiou (BMC, 2018)
Abstract Background Henoch-Schönlein purpura (HSP) is a common vasculitis in childhood characterized by purpura, arthritis, abdominal pain and renal involvement. However, bullous HSP is a rare cutaneous manifestation, and a few cases have been reported. Case presentation Herein, we report a 15-year-old male with bullous HSP who presented with severe abdominal pain and hemorrhagic bullous lesions over his lower extremities. He was treated with corticosteroid, after which the symptoms improved dramatically. No recurrence was noted after follow-up, though scarring was present. We also reviewed the literature related to bullous HSP and identified 39 cases, most of whom were treated with corticosteroids. Conclusion Clinicians should be aware of the atypical types of HSP, including bullous HSP. Most patients with bullous HSP have a good prognosis.